2018
DOI: 10.1530/erc-17-0288
|View full text |Cite
|
Sign up to set email alerts
|

ROS-induced near-homozygous genomes in thyroid cancer

Abstract: A near-homozygous genome (NHG) is especially seen in a subset of follicular thyroid cancer of the oncocytic type (FTC-OV). An NHG was also observed in the metabolically relatively quiescent cell lines XTC.UC1, a model for FTC-OV, and in FTC-133, -236 and -238, the latter three derived from one single patient with follicular thyroid cancer. FTC-236 subclones showed subtle whole-chromosome differences indicative of sustained reciprocal mitotic missegregations. Reactive oxygen species (ROS) scavenger experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 57 publications
5
47
1
Order By: Relevance
“…Metabolic adaptation plays an important role in the development of cancers characterized by abundant malfunctioning mitochondria (oncocytic phenotype), including thyroid Hürthle cell carcinoma (HCC) 32 . HCCs typically show widespread loss of entire chromosomes, leading to a near-homozygous genome (NHG) [7][8][9]13,21 . The loss of entire chromosomes has been attributed to aberrant interactions with reactive oxygen species (ROS) 21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Metabolic adaptation plays an important role in the development of cancers characterized by abundant malfunctioning mitochondria (oncocytic phenotype), including thyroid Hürthle cell carcinoma (HCC) 32 . HCCs typically show widespread loss of entire chromosomes, leading to a near-homozygous genome (NHG) [7][8][9]13,21 . The loss of entire chromosomes has been attributed to aberrant interactions with reactive oxygen species (ROS) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…HCCs typically show widespread loss of entire chromosomes, leading to a near-homozygous genome (NHG) [7][8][9]13,21 . The loss of entire chromosomes has been attributed to aberrant interactions with reactive oxygen species (ROS) 21 . Interestingly, recent findings showed that ROS vary with the cell cycle phase and reach their highest levels during mitosis 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CH2879, JJ012, and SW1353 cells were seeded on sterilized 3-Aminopropyltriethoxysilane (APES) coated slides (5 × 10 5 to 1 × 10 6 cells/slide). After overnight attachment, cultures were irradiated at 0 or 5 Gy of y-radiation using a 137 C source (YXLON, Comet Technologies, Shelton, CT, USA), and were allowed to recover for 2 h or 24 h. Slides were fixed with 4% formaldehyde at 37 • C, washed with PBS/0.05% Tween20, and permeabilized with 100% ice-cold methanol at −20 • C as described previously [59]. Blocking was performed with PBS/1% BSA/0.05% Tween20 for 30 min at 37 • C. Slides were stained with primary antibodies against geminin (1:500, 10802-1-AP, Proteintech, Manchester, UK) and RAD51 (1:500, clone 14B4, GeneTex, Irvine, CA, USA) for 1 h at 37 • C. After washing, slides were incubated with an Alexa Fluor 488/549 secondary antibody mix supplemented with 0.5 µM Hoechst 33342 for 1 h at 37 • C. Slides were washed, covered with ProLong Gold Antifade Reagent (Invitrogen Life-Technologies), and a LSM 700 laser scanning confocal microscope (Carl Zeiss, Oberkochen, Germany) was used to acquire images of regions of interest.…”
Section: Rad51 Foci Assaymentioning
confidence: 99%